Impementasi Pembelajaran Fisika Pokok Bahasan Elastisitas Melalui Inquiry Based Learning di SMA Negeri 2 Donggo - Soekarman Soekarman (Jurnal Paedagogy, 2021)
The purpose of this study was to describe the feasibility of the inquiry learning process of elasticity material using the P4TK IPA Hooke Law learning unit in class XI IPA students at SMA Negeri 2 Donggo. In the learning process of the elasticity material using Hooke's Law learning unit with an inquiry learning model with 6 levels. This research method used descriptive method. The research instrument used observation, interview, and tests. The data analysis technique used quantitative descriptive analysis. The results of this study indicate that the inquiry learning process on the subject of Elasticity and Hooke's Law using the Hooke P4TK IPA Law Physics learning unit in class XI IPA students of SMA Negeri 2 Donggo can be implemented properly and student learning outcomes are 100% complete.